Targeting transcription factor pu.1 for improving neurologic outcomes after spinal cord injury - Shi, Yi; Zheng, Meige; Luo, Yang; Li, Jianjian; Ouyang, Fangru; Zhao, Yuanzhe; Wang, Jingwen; Ma, Zhida; Meng, Congpeng; Bi, Yihui; Cheng, Li; Jing, Juehua (Frontiers in Neuroscience, 2024)
Background After spinal cord injury (SCI), lipid metabolism dysregulation at the lesion site exacerbates secondary damage. The transcription factor pu.1 has been implicated as a negative regulator of multiple lipid metabolism-related genes and pathways. However, its role in post-SCI lipid metabolism remains unclear. Methods We employed a mouse model of complete T10 crush SCI. Non-targeted metabolomics and bioinformatics analysis were utilized to investigate lipid metabolism at the lesion site after SCI. Polarized light imaging was used to evaluate the presence of cholesterol crystals. DB1976, a specific inhibitor of pu.1, was administered to examine its impact on local lipid metabolism after SCI. Immunofluorescence staining was performed to assess pu.1 expression and distribution, and to evaluate lipid droplet formation, astrocytic/fibrotic scar development, inflammatory cell infiltration, and tight junctions within the vasculature. Results Non-targeted metabolomics and bioinformatics analyses revealed significant alterations in lipid metabolism components after SCI. Moreover, immunofluorescence staining and polarized light imaging demonstrated substantial BODIPY+ lipid droplet accumulation and persistent cholesterol crystal formation at the lesion site after SCI. Increased pu.1 expression was predominantly observed within macrophages/microglia at the lesion site after SCI. DB1976 treatment significantly mitigated lipid droplet accumulation and cholesterol crystal formation, reduced CD68+ macrophage/microglial infiltration, and attenuated fibrotic scar formation. Moreover, DB1976 treatment promoted the expression of claudin-5 and zonula occludens-1 between vascular endothelial cells and enhanced GFAP+ glial connectivity after SCI. Conclusion Our study reveals a significant correlation between lipid metabolism disturbance post-SCI and transcription factor pu.1 upregulation, specifically in macrophages/microglia at the lesion site. Thus, targeted pu.1 modulation has the potential to yield promising results by substantially diminishing the deposition of lipid metabolism byproducts at the lesion site and fostering a milieu conducive to SCI repair.